A Study of Physical Fitness and Enjoyment on Virtual Running for Exergames. (30th April 2021) - Khundam, Chaowanan; Nöel, Frédéric
Abstract : Virtual Reality (VR) technology has advanced forward in everyday life where virtual fitness is possible through physically moving around in the real world. Exergame is a video game for exercise aimed at making exercise more fun. VR exergame applies these trends together for virtual fitness with immersive game play. The VR locomotion is traveling in VR, which is commonly used in adventure role-playing games (RPG). Virtual running can be applied as a locomotion technique for VR exergames. The design of virtual running in VR exergames should be considered as an exercise for fitness and also for enjoyment. This paper proposed two motion-based locomotion techniques: ArmSwing and Squat for virtual running, which are considered as aerobic and strength exercise. These two postures were used to study how physical exertion affected players while interacting in the test scene. Usability, motion sickness, and enjoyment were assessed to analyze the differences of each posture. The results showed that motion sickness and enjoyment of ArmSwing and Squat were not different, while usability was different where ArmSwing was rated higher than Squat. The results from the interviews suggest that most players preferred aerobic exercise (ArmSwing) more than strength exercise (Squat) for a long period of exercise. However, for a short period of exercise, players preferred strength exercise more than aerobic exercise. The adventure-based RPG for exercise needs a solution design appropriate for virtual running in VR, and our results can be a guideline for developers in order to handle motion-based locomotion for VR exergames.